The autophagic inhibitor 3-methyladenine potently stimulates PKA-dependent lipolysis in adipocytes - Heckmann, Bradlee L (Blackwell Publishing Ltd, 2013)
BACKGROUND AND PURPOSE: The class III PI3K inhibitor, 3-methyladenine (3-MA), is commonly used to selectively block autophagy. Recent findings suggest a strong relationship between autophagy and lipid turnover. Here, we explore the effect of 3-MA on adipocyte lipolysis. EXPERIMENTAL APPROACH: Assays were performed in 3T3-L1 cells. Cells were treated with 3-MA and wortmannin, a pan PI3K and autophagy inhibitor. Pharmacological and genetic manipulation of endogenous autophagic and lipolytic pathways was used to ascertain the contribution of 3-MA to the observed effects on lipolysis. KEY RESULTS: 3T3-L1 cells that were exposed to 3-MA showed a consistent increase in lipolysis, approximately 50% over basal levels. The effect of 3-MA was not secondary to autophagic inhibition as treatment of 3T3-L1 cells with wortmannin yielded no such changes. Dosing and time course experiments showed that 3-MA's ability to activate lipolysis was more sensitive than its inhibitory effect on autophagy. Knockdown of adipose triglyceride lipase (ATGL) negated the stimulatory effect of 3-MA by >90%, indicating that 3-MA enhanced ATGL-dependent hydrolysis of triacylglycerols. Additionally, the lipolytic effect of 3-MA was dependent on the activation of PKA and 3-MA induced a rapid and potent elevation of intracellular cAMP levels in adipocytes. CONCLUSIONS AND IMPLICATIONS: Cumulatively, we show that 3-MA potently modulated a cellular mechanism and its underlying signalling pathways not associated with autophagy. Furthermore, we describe a novel stimulatory effect on a major signalling pathway. Our findings provide valuable information to studies employing 3-MA as a specific inhibitor for PI3K and autophagy.